The Effect of Leadership and Organizational Culture on Employee Performance - Tianingrum, Atikah Sofa (Pandawan, 2022)
Currently, many construction companies offer construction services for Pile Foundation work and Bored Pile or Struss Pile for Buildings, Bridges, BTS Towers, Residential Houses, Shophouses, Hotels and the like using the Bored Pile or Strauss Pile method. The problem that exists is because of the influence of employee performance on construction where there are still some employees who are not satisfied with the leadership. This study aims to determine the effect of influence on employee performance and to see the influence of Organizational Culture on employee performance. This study tested three hypotheses with data sources originating from respondents from PT. Queen of the Great Foundation. Information, primary and secondary data in this study were only obtained from PT. Queen of the Great Foundation. The population and sample of this study were all employees of PT. The Great Foundation Queen of various divisions that opened 90 people. This study uses a quantitative approach method. The data collection technique used primary data in the form of a questionnaire. The data analysis technique of this research used the Structural Equation Modeling-Partial Least Square (SEM-PLS) method. This study shows that 1) Leadership has a positive and significant effect on Employee Performance, 2) Leadership has a positive and significant influence on Organizational Culture, 3) Organizational culture has a positive and significant influence on employee performance.